A post-market, randomized, controlled, prospective study evaluating intrathecal pain medication versus conventional medical management in the non-cancer, refractory, chronic pain population (PROSPER). (2nd November 2022) - Pope, Jason E.; Jassal, Navdeep; Sayed, Dawood; Patterson, Denis; McDowell, Gladstone; Bux, Anjum; Lim, Phillip; Chang, Eric; Nairizi, Ali; Grodofsky, Samuel; Deer, Timothy R
ABSTRACT: Introduction: Intrathecal therapy has been limited by non-randomized prospective studies, particularly for those suffering from non-cancer. Further, no prospective, randomized studies investigating the efficacy, safety, and utilization of intrathecal polyanalgesic consensus guidelines exist. Methods: After IRB approval, patients were enrolled in a 1:1 fashion for intrathecal drug delivery (IDD) or conventional management (CMM), employing standard of care, excluding intrathecal drug delivery, based on the principal investigator's discretion. They were followed 3, 6, 9, and 12 months. Assessments included PROMIS 29, NPRS, and PriceMonkey. Results: Seventy-nine patients were screened, 54 patients were enrolled: 26 to IDD and 28 to CMM. At 3 months, there was no measurable difference in pain improvement in either subgroups within the CMM for chronic pain-related syndromes (CPRS) or failed back and related spine disorders (FBRS). For the IDD, early and maintained benefit from the baseline was statistically achieved. Cost analysis of pump to CMM breakeven was 4.5 months. There were no adverse events related to compounded intrathecal medications. Conclusion: This is the first randomized prospective, multicenter study investigating the safety, cost, and efficacy of off-label medications for intrathecal therapy, as compared to conventional management, and suggests early detection of improvement, cost savings, safety of intrathecal compounded medication use, and safety and efficacy of employing the PACC guidance.